The Effects of the MBKM Kampus Mengajar Program on Pre-Service Teachers’ Teaching Competencies - Yamin, Warahma Apriliani; Farmasari, Santi; Zamzam, Ahmad (Program Studi Pendidikan Bahasa Inggris, 2024)
This study aims to describe the effect of the Kampus Mengajar program on pre-service teachers’ teaching competencies. In this study, the data collection technique used was semi-structured interviews, where semi-structured interviews are interviews that combine structured interviews and unstructured interviews. Based on the research question, what is the effect of the Kampus Mengajar program on pre-service teachers' teaching competencies. In this study, 15 interviewees who had participated in the Kampus Mengajar program were taken, and they were given interview questions regarding 4 aspects of teaching competence: pedagogic, personality, professional, and social. The research findings show that the results of interviews conducted with 15 interviewees show that the percentage of interviewees who answered “YES” to 17 questions regarding 4 aspects of teaching competence is more dominant than those who answered “NO”, namely 12 people out of 17 questions with a percentage of 100%, which shows that the Kampus Mengajar program has a positive effect on pre-service teachers’ teaching competencies. The Kampus Mengajar program significantly enhances prospective teachers' teaching competence by providing hands-on experience, improving pedagogical, personal, professional, and social skills essential for effective teaching. Participants reported gains in lesson planning, learning evaluation, empathetic behavior, mastery of subject matter, and collaborative teaching. However, challenges such as limited evaluation experience, short interaction periods, and difficulties with curriculum mastery highlight areas for improvement to maximize the program's impact.